A 3.3 Gbps CCSDS 123.0-B-1 Multispectral & Hyperspectral Image Compression Hardware Accelerator on a Space-Grade SRAM FPGA - Tsigkanos, Antonis; Kranitis, Nektarios; Theodorou, George; Paschalis, Antonis (IEEE transactions on emerging topics in computing, 2021)
The explosive growth of data volume from next generation high-resolution and high-speed hyperspectral remote sensing systems will compete with the limited on-board storage resources and bandwidth available for the transmission of data to ground stations making hyperspectral image compression a mission critical and challenging on-board payload data processing task. The Consultative Committee for Space Data Systems (CCSDS) has issued recommended standard CCSDS-123.0-B-1 for lossless multispectral and hyperspectral image compression. In this paper, a very high data-rate performance hardware accelerator is presented implementing the CCSDS-123.0-B-1 algorithm as an IP core targeting a space-grade FPGA. For the first time, the introduced architecture based on the principles of C-slow retiming, exploits the inherent task-level parallelism of the algorithm under BIP ordering and implements a reconfigurable fine-grained pipeline in critical feedback loops, achieving high throughput performance. The CCSDS-123.0-B-1 IP core achieves beyond the current state-of-the-art data-rate performance with a maximum throughput of 213 MSamples/s (3.3 Gbps @ 16-bits) using 11 percent of LUTs and 27 percent of BRAMs of the Virtex-5QV FPGA resources for a typical hyperspectral image, leveraging the full throughput of a single SpaceFibre lane. To the best of our knowledge, it is the fastest implementation of CCSDS-123.0-B-1 targeting a space-grade FPGA to date.